Rancang Bangun Sistem Informasi Kepegawaian Berbasis Web Pada PT.Portal Indonesia Group - Altarisa, Nabila Syiva; Mardiani, Mardiani (MDP Student Conference, 2024)
The purpose of creating a web-based personnel information system design application at PT Portal Indonesia Group is to assist in managing and monitoring personnel data related to employee data, attendance, promotions, demotions, transfers, layoffs, rewards and punishments which can be used by directors and admins. Apart from admins and directors, this application can be used by employees to assist employees in applying for leave and making attendance independently and can be used by prospective applicants to apply for jobs at the company. In the design and construction of the personnel information system, supporting applications were created, namely Visual Studio Code, MySql, Laravel Framework, and XAMPP. The methodology in the process of developing a personnel information system is the RUP (rational unified process) method. The result of creating a personnel application is that it can help and enable the PT.Portal Indonesia Group admin section to manage personnel data